An Analysis of Student's Recount Text: An SFL Approach - Faradina, Widya Nur; Emilia, Emi (Pusat Pelatihan, Riset, dan Pembelajaran Bahasa, 2024)
This paper reports on the results of a study aiming to investigate the student’s ability to write recount text of a university student in Bandung. The study was conducted using the theory of Systemic Functional Linguistics (SFL), especially functional grammar, in terms of the Transitivity, Mood and Modality system. The study used a case study on text analysis. A text, which is a recount text written by a higher achiever university student, was analysed using the Transitivity, Mood and Modality system. In terms of the Transitivity system, the result indicates the writer’s adequate syntactic compression and rich lexico-grammatical patterns. Moreover, in terms of the Mood and Modality system, the text shows the writer’s ability to infuse, temper, negotiate, and constrain the experiential meanings in the Mood that is in focus. Hence, the writer is categorized as a mature and critical writer, and the text is appropriate to be used as a model text. Research on text analysis using SFL of different genres of text and how the teaching of writing should be conducted to help improve students’ writing ability is recommended.